Diagnostic Accuracy of Serum Prostate Specific Antigen and Gleason Score in Determining the Presence of Skeletal Metastasis in Prostate Cancer Patients: a Pakistani Perspective - Taimoor Nasir; Syeda Neha Aamer; Saman Waqar; Wafa Omer (Journal of Rawalpindi Medical College)
Objective: